Temporal and geographic dynamics of bovine viral diarrhea virus in American countries - Spetter, Lucas Maximiliano (2022)
Bovine viral diarrhea virus (BVDV) is a worldwide distributed pathogen of livestock classified into three species, BVDV-1 (Pestivirus A), BVDV-2 (Pestivirus B), and HoBi-like pestivirus (HoBiPeV; Pestivirus H). Despite being considered endemic in several regions of the Americas, the spatiotemporal distribution of BVDV is scarcely known. This study aimed to reconstruct the population dynamics of BVDV in American countries. The analyses performed with the partial 5´UTR gene showed that BVDV-1 and -2 would have started their diversification in the 1670s and 1790s in the United States, whereas HoBiPeV probably emerged in the 1980s in Brazil. No evident geographic clustering was observed in the Bayesian trees, which may indicate that multiple introductions events would have occurred following the first introduction. This study provides new insights into BVDV dynamics, although further analyses including sequences from other American countries and continents will help to expand the knowledge of BVDV evolution and transmission.